An Adaptif Teaching in Mathematics as a solution for e-learning : Study Literature - dame ifa sihombing (Sepren, 2022)
Supporting students' math skills requires teachers to continually adapt their instruction in response to meeting students' instructional needs. To explore what it means to be an adaptive teacher, this study conducted a literature study starting from adaptive teaching in mathematics. In this study, 11 articles were found that identified the importance of (a) a stimulus, or something that teachers should follow; (b) metacognition and teacher reflection, or interpretation and analysis; and (c) the teacher's actions, or responses. Additional findings highlight the importance of mathematics education research to take a closer look: (a) how the curriculum can serve as a stimulus that aids adaptive teaching practice; (b) the idea that teachers reflect directly on students' stimuli, learning processes, or their own actions; and (c) additional teacher responses, including managing class discourse, modifying curriculum materials, or selecting teaching tools.